2015
DOI: 10.1093/mnras/stv565
|View full text |Cite
|
Sign up to set email alerts
|

The Lyman α signature of the first galaxies

Abstract: We present the Cosmic Lyman-α Transfer code (COLT), a massively parallel Monte-Carlo radiative transfer code, to simulate Lyman-α (Lyα) resonant scattering through neutral hydrogen as a probe of the first galaxies. We explore the interaction of centrally produced Lyα radiation with the host galactic environment. Lyα photons emitted from the luminous starburst region escape with characteristic features in the line profile depending on the density distribution, ionization structure, and bulk velocity fields. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 111 publications
1
101
0
Order By: Relevance
“…Although the recombination luminosity in Lyα is higher than that in Hα, in reality Lyα photons are more likely to scatter in the neutral IGM (e.g. Dijkstra & Wyithe 2007;Smith et al 2015), and thus the observed flux in Lyα may be substantially lower than implied by the intrinsic luminosity. Because of the hard spectra of massive Pop III stars, strong nebular emission, particularly in the He II λ1640 line, has been suggested as a possible observable signature of metal-free Pop III galaxies (e.g.…”
Section: Luminositymentioning
confidence: 97%
“…Although the recombination luminosity in Lyα is higher than that in Hα, in reality Lyα photons are more likely to scatter in the neutral IGM (e.g. Dijkstra & Wyithe 2007;Smith et al 2015), and thus the observed flux in Lyα may be substantially lower than implied by the intrinsic luminosity. Because of the hard spectra of massive Pop III stars, strong nebular emission, particularly in the He II λ1640 line, has been suggested as a possible observable signature of metal-free Pop III galaxies (e.g.…”
Section: Luminositymentioning
confidence: 97%
“…to produce the necessary offset, where we have normalized the gas temperature according to T 4 ≡ T/(10 4 K), see the discussion following equation (34) in Smith et al (2015). Assuming an approximately isothermal density profile, clump A would have τ 0 10 11 if it remained neutral.…”
Section: Basic Observational Propertiesmentioning
confidence: 99%
“…As predicted by Partridge & Peebles (1967), proto-galactic star formation would produce powerful intrinsic Lyα luminosities, although the increasing neutral hydrogen fraction in the diffuse intergalactic medium (IGM) significantly suppresses Lyα transmission for sources at z > 6.5 (Dijkstra 2014; Mesinger et al 2015). Still, galaxies with strong Lyα emission are more likely to be detected with substantial outflows or clustered within locally ionized bubbles and web-like morphologies (Jensen et al 2013;Kakiichi et al 2015;Smith et al 2015). Despite attenuation from the neutral IGM one might hope to infer properties of the emission source, galaxy, and IGM based on the altered Lyα line profile, physical size of the Lyα emitting region, continuum spectral energy distribution (SED), and relative strength of Lyα, Hα, and He ii 1640 Å nebular emission lines (Schaerer 2002;Johnson et al 2009;.…”
Section: Introductionmentioning
confidence: 96%
“…To construct the density profile for the gaseous component, we adopt an isothermal power law of the form ∼ r −2 , as it provides a good description of a virialized system (Binney & Tremaine 2008). Following Smith et al (2015), we consider a non-cuspy 'core', consistent with observations of low surface brightness galaxies (e.g. Kormendy et al 2009).…”
Section: Model Galaxiesmentioning
confidence: 99%